How to be both : a novel - Smith, Ali, 1962- (Pantheon, 2014)
"The brilliant Booker-nominated novel from one of our finest authors: How to Be Both is a daring, inventive tale that intertwines the stories of a defiant Renaissance painter and a modern teenage girl. How can one be both--near and far, past and present, male and female? In Ali Smith's new novel, two extraordinary characters inhabit the spaces between categories. In one half of the book, we follow the story of Francescho del Cossa, a Renaissance painter in fifteenth-century Italy who assumes a duel identity, living as both a man and a woman. In the novel's other half, George, a contemporary English teenage girl, is in mourning after the death of her brilliant, rebellious mother. As she struggles to fill the void in her life, George finds her thoughts circling again and again around a whimsical trip she and her mother once made to Italy, to see a certain Renaissance fresco... These two stories call out to each other in surprising and deeply resonant ways to form a veritable literary double-take, bending the conventions of genre, storytelling, and our own preconceptions"--